A stator resistance estimation of induction motor using fuzzy logic - Mohd Akmal, Rohani (2010)
During the operation of induction motor, stator resistance changes incessantly with the temperature of the working machine. This situation may cause an error in rotor resistance estimation of the same magnitude and will produce an error between the actual and estimated motor torque which can leads to motor breakdown in worst cases. Therefore, this project will propose an approach to estimate stator resistance of induction motor using fuzzy logic. Then, a correction will be making to ensure the stabilization of the system. Generally, this project can be divided into three parts which are design the induction motor by using the mathematical equation, design Fuzzy Logic estimator to estimate the value of stator resistance R, and make the correction of stator resistance,R. The MATLAB simulink is used in order to design the induction motor. Secondly, Fuzzy Logic Toolbox is used to design fuzzy logic estimator and finally the correction of R is make.